Pacemakers charging using body energy - Dinesh Bhatia; Sweeti Bairagi; Sanat Goel; Manoj Jangra (Wolters Kluwer Medknow Publications, 2010)
Life-saving medical implants like pacemakers and defibrillators face a big drawback that their batteries eventually run out and patients require frequent surgery to have these batteries replaced. With the advent of technology, alternatives can be provided for such surgeries. To power these devices, body energy harvesting techniques may be employed. Some of the power sources are patient's heartbeat, blood flow inside the vessels, movement of the body parts, and the body temperature (heat). Different types of sensors are employed, such as for sensing the energy from the heartbeat the piezoelectric and semiconducting coupled nanowires are used that convert the mechanical energy into electricity. Similarly, for sensing the blood flow energy, nanogenerators driven by ultrasonic waves are used that have the ability to directly convert the hydraulic energy in human body to electrical energy. Another consideration is to use body heat employing biothermal battery to generate electricity using multiple arrays of thermoelectric generators built into an implantable chip. These generators exploit the well-known thermocouple effect. For the biothermal device to work, it needs a 2°C temperature difference across it. But there are many parts of the body where a temperature difference of 5°C exists - typically in the few millimeters just below the skin, where it is planned to place this device. This study focuses on using body heat as an alternative energy source to recharge pacemaker batteries and other medical devices and prevent the possibility of life-risk during repeated surgery.